Risk factors associated with children who runaway or are reported missing - Hutchings, Emma Lauren (2017)
The overarching aim of this thesis is to further understanding and knowledge of risk factors relevant to children who runaway. More specifically to; identify risk factors most relevant to children running away; establish whether risk factors can be used to distinguish between those children reported missing once versus those reported on multiple occasions; and evaluate assessment methods currently being used with this group.